2001
DOI: 10.1177/0148607101025005260
|View full text |Cite
|
Sign up to set email alerts
|

Choline Deficiency Causes Reversible Hepatic Abnormalities in Patients Receiving Parenteral Nutrition: Proof of a Human Choline Requirement: A Placebo‐Controlled Trial

Abstract: Choline deficiency is a significant contributor to the development of TPN-associated liver disease. The data suggest choline is a required nutrient for long-term home TPN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(109 citation statements)
references
References 60 publications
6
102
1
Order By: Relevance
“…Interestingly, smoking is associated with significantly lower PCho concentrations and the reasons for this are unknown [8]. Declines and/ or lower levels of plasma or SCho have been found after major surgery [41], traumatic head injury [40] and more gradually during long-term parenteral nutrition [42]. These and other factors leading to abnormal choline levels are summarized in Box 3.…”
Section: Choline Values In Health Acs and Other Diseasesmentioning
confidence: 99%
“…Interestingly, smoking is associated with significantly lower PCho concentrations and the reasons for this are unknown [8]. Declines and/ or lower levels of plasma or SCho have been found after major surgery [41], traumatic head injury [40] and more gradually during long-term parenteral nutrition [42]. These and other factors leading to abnormal choline levels are summarized in Box 3.…”
Section: Choline Values In Health Acs and Other Diseasesmentioning
confidence: 99%
“…Deficiencies of both taurine and choline have been documented in small (n 50) retrospective studies of patients receiving long-term HPN and are associated with increased biochemical markers of liver function. 101 …”
mentioning
confidence: 99%
“…There is considerably less evidence of a benefit of taurine supplementation in adults, with a reduction in aspartate aminotransferase levels being reported in a single small study of adults receiving long-term parenteral nutrition (47) . Similarly, small-scale trials of choline supplementation in adults have demonstrated that both parenteral choline and high-dose oral lecithin can increase plasma choline concentrations (40,41,86) . This outcome has been shown to be associated with a reduction in hepatic steatosis, assessed by computerised tomography scanning, and improvements in plasma ALP, alanine aminotransferase and aspartate aminotransferase concentrations (41) .…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Similarly, small-scale trials of choline supplementation in adults have demonstrated that both parenteral choline and high-dose oral lecithin can increase plasma choline concentrations (40,41,86) . This outcome has been shown to be associated with a reduction in hepatic steatosis, assessed by computerised tomography scanning, and improvements in plasma ALP, alanine aminotransferase and aspartate aminotransferase concentrations (41) . Further larger trials investigating the possible beneficial effects of both choline and taurine are ongoing.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation